2017
DOI: 10.1111/bju.13955
|View full text |Cite
|
Sign up to set email alerts
|

The new generation super‐mini percutaneous nephrolithotomy (SMP) system: a step‐by‐step guide

Abstract: ObjectiveTo present our novel miniaturised endoscopic system and describe a step-by-step guide for successful implementation of the super-mini percutaneous nephrolithotomy (SMP). Patients and MethodsThe new-generation SMP endoscopic system consists of (i) a 40 000-pixel super-mini nephroscope with an 8.0-F outer diameter and 7.5-F inner diameter dismountable sheath, and (ii) a newly designed irrigation-suction sheath available in either 12 F or 14 F. The irrigation-suction sheath is a twolayered metal structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 3 publications
0
32
0
Order By: Relevance
“…These developments include miniaturized PCNL equipment and flexible ureteroscopes. The new super-mini-PCNL (SMP) system requires a small percutaneous tract for access, so there is less blood loss and there is also effective stone clearance, the visual field is good, and the operation duration is short, with easy operation [12,13]. Flexible ureterorenoscopy (URS) does not require a new tract for access because it can use natural ones such as the urethra, ureter, or renal pelvis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These developments include miniaturized PCNL equipment and flexible ureteroscopes. The new super-mini-PCNL (SMP) system requires a small percutaneous tract for access, so there is less blood loss and there is also effective stone clearance, the visual field is good, and the operation duration is short, with easy operation [12,13]. Flexible ureterorenoscopy (URS) does not require a new tract for access because it can use natural ones such as the urethra, ureter, or renal pelvis.…”
Section: Introductionmentioning
confidence: 99%
“…Most urologists tend to use either digital flexible URS or single-tract miniaturized PCNL to treat renal stones, with great success [15,16]. However, these techniques cannot resolve all cases with multiple kidney stones, resulting in a low stone-free rate and complications in some patients [12,14]. Previous reports have demonstrated that miniaturized PCNL combined with digital flexible URS is safe for pediatric [17] and adult patients [18] with multiple kidney stones and for adults with large stones [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…This design restricted irrigation flow once a laser fibre or pneumatic lithotripter device was inserted, leading to suboptimal visualization requiring longer operative times. To overcome this limitation, the new-generation SMP utilizes a novel irrigation-suction sheath to improve irrigation, which also enables the use of more efficient stone fragmentation devices to improve stone clearance [39] .…”
Section: Super-mini-pcnl (Smp) and Authors' Experiencementioning
confidence: 99%
“…The SMP telescope has a 1.4 mm working diameter with a 40 000-pixel resolution. The sheath consists of a two-layered metal structure, available in either 12 or 14 Fr [39] . The space between the two layers of the sheath forms an independent irrigation channel, and the central lumen of the sheath works as a conduit for continuous suction.…”
Section: Super-mini-pcnl (Smp) and Authors' Experiencementioning
confidence: 99%
“…To overcome these deficiencies of mini‐PCNL, Prof. Guohua Zeng developed super‐mini‐PCNL (SMP) . The basic components of the SMP system are a miniaturized nephroscope with an irrigation‐suction sheath.…”
mentioning
confidence: 99%